Proteome analysis of rice (Oryza sativa L.) mutants reveals differentially induced proteins during brown planthopper (Nilaparvata lugens) infestation - Sangha, Jatinder; Chen, Yolanda; Kaur, Jatinder; Khan, Wajahatullah; Abduljaleel, Zainularifeen; Alanazi, Mohammed; Mills, Aaron; Adalla, Candida; Bennett, John; Prithiviraj, Balakrishnan; Jahn, Gary; Leung, Hei (MDPI, 2013)
Although rice resistance plays an important role in controlling the brown planthopper (BPH), Nilaparvata lugens, not all varieties have the same level of protection against BPH infestation. Understanding the molecular interactions in rice defense response is an important tool to help to reveal unexplained processes that underlie rice resistance to BPH. A proteomics approach was used to explore how wild type IR64 and near-isogenic rice mutants with gain and loss of resistance to BPH respond during infestation. A total of 65 proteins were found markedly altered in wild type IR64 during BPH infestation. Fifty-two proteins associated with 11 functional categories were identified using mass spectrometry. Protein abundance was less altered at 2 and 14 days after infestation (DAI) (T1, T2, respectively), whereas higher protein levels were observed at 28 DAI (T3). This trend diminished at 34 DAI (T4). Comparative analysis of IR64 with mutants showed 22 proteins that may be potentially associated with rice resistance to the brown planthopper (BPH). Ten proteins were altered in susceptible mutant (D1131) whereas abundance of 12 proteins including S-like RNase, Glyoxalase I, EFTu1 and Salt stress root protein “RS1” was differentially changed in resistant mutant (D518). S-like RNase was found in greater quantities in D518 after BPH infestation but remained unchanged in IR64 and decreased in D1131. Taken together, this study shows a noticeable level of protein abundance in the resistant mutant D518 compared to the susceptible mutant D1131 that may be involved in rendering enhanced level of resistance against BPH.